THE PROBLEM OF BALDNESS AND MODERN POSSIBILITIES OF TREATMENT (E Global Congress, 2023)
The problem of premature hair loss (alopecia) gives rise to great scientific and practical interest. This is due to the prevalence and steady incidence rate, the presence of acquired and inherited forms of alopecia, which are difficult for treatment. Alopecia - pathological process in which there are persistent or temporary, total or partial loss of hair or lack of them. This problem occurs in both children and adults, men and women almost equally. Despite the high quantity of researches and existing therapeutic methods of various forms of alopecia, the treatment is still not adequate and remains a big problem for public health practice. To solve this problem, in recent years, attend to meticulously study of structural and morphological characteristics of the skin and scar tissue in the focus, to research of hormonal imbalance and adopt a method of follicular microautotransplantation.